A kind of putty for rail transportation based on bio-based unsaturated polyester resin

By increasing the proportion of bio-based materials and adding bio-based components, combining acetylated modified filler and silane-coupled talc powder, the problem of insufficient flexibility and UV resistance on high-speed trains and high-speed rail is solved, and a higher level of flexibility is achieved The adhesion, impact resistance and stability are adapted to the needs of high-altitude and high-light areas.

CN118638445BActive Publication Date: 2025-01-10ANHUI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411110401.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-01-10
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The existing atomic ash for high-speed trains and high-speed railways perform poorly in terms of flexibility, adhesion and stability, especially inadequate UV resistance under ultraviolet light exposure in plateaus and high sunlight intensity areas.

Method used

Using bio-based unsaturated polyester resin, by increasing the proportion of bio-based materials, combined with raw materials such as bio-based ethylene glycol, bio-based fumaric acid, bio-based oleic acid and bio-based hydrogenated castor oil, enhance the adhesion and flexibility of atomic ash. and improve the UV and anti-aging properties through acetylation modified bio-based filler and silane-coupled modified talc powder.

Benefits of technology

It significantly improves the adhesion and flexibility of atomic ash, enhances impact strength, and provides better UV resistance and stability in high-altitude and high-light areas, meeting the needs of complex environments of rail transit vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118638445B_ABST
    Figure CN118638445B_ABST
Patent Text Reader

Abstract

The invention discloses a putty for rail transit based on bio-based unsaturated polyester resin, wherein the putty is prepared from unsaturated polyester resin, cobalt isooctanoate, active diluent, high mesh talc, low mesh talc, pigment, polymerization inhibitor, dispersant, defoamer, anti-settling thixotropic agent and bio-based filler as raw materials, wherein the unsaturated polyester resin contains a large amount of bio-based components. The putty of the invention is fine and easy to scrape, has high adhesion, high flexibility, high bending performance, high impact resistance and excellent anti-ultraviolet and anti-aging capabilities, and by adding bio-based monomers and fillers, the amount of petroleum-based materials is reduced. As an environmentally friendly product, it is conducive to guiding green technology innovation and improving the global competitiveness of industry and economy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of coatings, and in particular relates to a putty for rail transit based on a bio-based unsaturated polyester resin. Background Art

[0002] Putty, commonly known as putty, is composed of main putty and curing agent. It is a new type of filling material that is easy and quick to use. It is widely used in various metal product fields that need to be filled and repaired, such as train manufacturing, ship manufacturing, and automobile manufacturing. It effectively fills and modifies defects such as base material pits, pinholes, cracks, and welds to meet the requirements of the flatness and smoothness of the base material surface before topcoat. The main ingredients of the putty are mostly unsaturated polyester resin and filler; the ingredients of the curing agent are generally initiators and plasticizers, which play a role in initiating polymerization and enhancing performance. Unsaturated polyester resin is the main body of the putty. After initiation, polymerization occurs, rapid molding and curing occurs, and it adheres to the surface of the object. Diluents such as styrene and other modified materials are generally added to the filler to optimize performance.

[0003] Based on the characteristics of high-speed and high-frequency moving carriers such as EMU subways, and the complexity of their operation in large areas (plateaus and high-light areas, etc.), the atomic putty used in rail transit is required to have good weather resistance and stability, as well as good temperature change resistance.

[0004] Patent CN104177901A "A special putty for high-speed trains and its preparation method" discloses a putty specially used for filling defects on the outer surface of high-speed train bodies. It consists of two parts: main putty and curing agent. The main putty includes: unsaturated polyester resin, E-60 epoxy acrylic resin, styrene, composite accelerator, fumed silica, titanium dioxide, and talcum powder. The unsaturated polyester resin is produced by polycondensation reaction of diethylene glycol, N-2 polyurethane resin, E-200 polyethylene glycol, maleic anhydride, and styrene. Although the flexibility, impact strength, adhesion and other properties of the obtained putty can meet the needs of filling defects on the outer surface of high-speed train bodies, there is still room for improvement, and the materials used are basically petroleum-based materials.

[0005] Patent CN110616005B "A high-iron putty and its preparation method" provides a high-iron putty. The main innovation of the putty is the use of triols and diols in combination. Under the action of maleic anhydride, tetrahydrophthalic anhydride and preferably air-drying monomer trimethylolpropane diallyl ether, it can quickly dry and dry at room temperature, and can be quickly constructed, but it will cause a significant decrease in adhesion on different substrates. At the same time, linoleic acid is added as a modifier in the patent. Although the impact resistance and flexibility of the putty after curing can be improved to a certain extent by combining with the saturated fatty acid myristic acid, it will also cause a decrease in adhesion.

[0006] In summary, the flexibility, adhesion and stability of the putty currently developed for high-speed trains and high-speed railways cannot meet the operating environment of high-speed railways. In addition, when high-speed trains and high-speed railways are running in plateaus and areas with high sunshine intensity, they are exposed to strong ultraviolet light, so the train body is also required to have good anti-ultraviolet performance. Summary of the invention

[0007] Based on the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a rail transit putty based on bio-based unsaturated polyester resin for the complex operating environment of rail transit vehicles, so as to increase the proportion of bio-based materials in the putty, improve adhesion and flexibility, and improve the stability of the putty and its anti-UV and anti-aging properties.

[0008] In order to achieve the purpose, the present invention adopts the following technical scheme:

[0009] The present invention first provides a bio-based unsaturated polyester resin, which is characterized in that the raw materials of the bio-based unsaturated polyester resin include petroleum-based components and bio-based components, and the composition of each raw material in terms of mass fraction is as follows:

[0010] Petroleum-based components: 15-18 parts of diethylene glycol, 10-18 parts of tetrahydrophthalic anhydride, 0.1-0.2 parts of hydroquinone, 10-15 parts of maleic anhydride, 30-36 parts of styrene for monomer, 2 parts of styrene for dilution;

[0011] Bio-based components: 6-15 parts of bio-based ethylene glycol, 5-10 parts of bio-based fumaric acid, 12-16 parts of bio-based oleic acid, and 5-9 parts of bio-based hydrogenated castor oil.

[0012] Furthermore, the mass fraction of the bio-based hydrogenated castor oil is preferably 5 to 5.5 parts. Bio-based hydrogenated castor oil can improve flexibility, but too high a content thereof will cause a decrease in adhesion.

[0013] The method for preparing the bio-based unsaturated polyester resin of the present invention comprises the following steps:

[0014] Adding diethylene glycol, tetrahydrophthalic anhydride, hydroquinone, maleic anhydride, styrene for monomer, bio-based ethylene glycol, bio-based fumaric acid, bio-based oleic acid and bio-based hydrogenated castor oil into a reaction kettle;

[0015] Introduce nitrogen, start stirring and keep the stirring speed at 150-250 rpm, and carry out the following reaction: heat to 165-185°C, keep stirring for 1-1.5 hours; heat to 190-210°C, keep stirring for 1.5-2 hours; continue to heat to 200-220°C, keep stirring for 3-4 hours;

[0016] After the reaction is completed, the acidity is adjusted to 60-70KOH / g (preferably 65KOH / g); then the temperature is lowered to 50-60°C, vacuum dehydrated for 0.5-2h, and styrene is added for dilution to obtain a bio-based unsaturated polyester resin.

[0017] The present invention further discloses an atomic putty for rail transit based on the above-mentioned bio-based unsaturated polyester resin, which comprises the following raw materials in parts by weight: 38-45 parts of bio-based unsaturated polyester resin, 0.5-0.8 parts of cobalt isooctanoate as an accelerator, 2-5 parts of active diluent, 30-33 parts of high-mesh talc powder, 16-20 parts of low-mesh talc powder, 1-2 parts of pigment, 0.5-1 parts of inhibitor, 0.2-0.4 parts of dispersant, 0.1-0.3 parts of defoaming agent, 2-3 parts of anti-settling thixotropic agent, and 2-4 parts of acetylated modified bio-based filler.

[0018] Furthermore, the active diluent is at least one of styrene and bio-based acrylic epoxy soybean oil, preferably styrene.

[0019] Furthermore, the polymerization inhibitor is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butyl)phenyl phosphite and 2,6-di-tert-butyl-4-methylphenol.

[0020] Furthermore, the pigment is at least one of titanium dioxide and iron oxide, and is preferably titanium dioxide ground by a three-roll mill.

[0021] Furthermore, the dispersant is at least one of sodium polyacrylate, sodium fatty acid methyl ester sulfonate and sodium alcohol ether sulfate.

[0022] Furthermore, the defoaming agent is at least one of a silicone defoaming agent, a polyether defoaming agent, a mineral oil defoaming agent and a high-carbon alcohol defoaming agent.

[0023] Further, the anti-settling thixotropic agent is at least one of polyamides, fumed silica, montmorillonite and cellulose. Further, the cellulose is at least one or more of hydroxyethyl cellulose, sodium hydroxymethyl cellulose and hydroxypropyl methyl cellulose. The anti-settling thixotropic agent can increase the thixotropic properties of the product.

[0024] Further, the talc is one or more of silane coupling modified talc, titanate modified talc, and aluminate modified talc, preferably silane coupling modified talc. The mesh number of the high-mesh talc is 800-1200 mesh, and the mesh number of the low-mesh talc is 300-600 mesh. Preferably, 600-mesh talc and 1000-mesh talc are compounded in a mass ratio of 1:1.9-2.

[0025] Furthermore, the acetylated bio-based filler is obtained by acetylation modification of at least one of alkaline lignin, sodium lignin sulfonate and calcium lignin sulfonate. The specific method of acetylation modification is: using pyridine as a catalyst, immersing lignin (at least one of alkaline lignin, sodium lignin sulfonate and calcium lignin sulfonate) in a mixed solution of acetic anhydride and pyridine (wherein the mass ratio of lignin, pyridine and acetic anhydride is 1:10:3), and then placing it in a closed reaction tank, heating it to 90-100°C, keeping it warm for 0.5 hours, then discharging the unreacted treatment liquid, drying, and obtaining the acetylated bio-based filler. Acetylation modification can improve the hydrophobicity of the filler and increase its compatibility with the resin.

[0026] Furthermore, the mass percentage of cobalt element in the cobalt isooctanoate is 8-12%.

[0027] The present invention also discloses a method for preparing the atomic ash for rail transit, comprising the following steps:

[0028] Add the bio-based unsaturated polyester resin and the inhibitor into a high-speed disperser, then add cobalt isooctanoate, and stir at a speed of 400-800 r / min for 20-60 min; then add the dispersant, defoamer and anti-settling thixotropic agent, stir at a speed of 800-1200 r / min for 15-30 min, and then add 1-3 parts of active diluent to adjust the viscosity of the mixture; then add high-mesh talc, low-mesh talc and acetylated modified bio-based filler, and continue to stir at a speed of 1200-1600 r / min for 1.5-3 h; finally, add the pigment and the remaining active diluent, and continue to stir at a speed of 1200-1600 r / min for 0.5-1 h; let the dispersed mixture stand for 0.5-1 h to obtain atomic putty.

[0029] The putty obtained by the invention has a consistency of 11-13 cm, has no crust, no unstirable lumps, no white spots, and has a smooth appearance without particles or sagging.

[0030] The putty obtained by the present invention can be used on a vehicle body for rail transit. When used, the putty and the curing agent are mixed and stirred evenly according to a mass ratio of 100:2, and then applied for use.

[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0032] 1. Compared with ordinary putty, the rail transit putty prepared by the present invention increases the proportion of bio-based materials in unsaturated resin and reduces the use of non-renewable materials such as petroleum-based materials. The use of renewable energy bio-based materials can accelerate the reduction of carbon emissions, which is conducive to guiding green technology innovation and improving the global competitiveness of industry and economy.

[0033] 2. The proportion of bio-based materials in the unsaturated polyester resin of the present invention is increased, so that the adhesion and flexibility of the putty product prepared based on it are better than those of ordinary putty, and the impact strength is also greatly improved, which is more suitable for the high-speed, high-strength, complex and changeable driving environment of rail transit trains.

[0034] 3. Rail transit trains are exposed to high intensity ultraviolet light when traveling in high-altitude and high-intensity areas. The addition of bio-based lignin greatly improves the anti-aging and anti-ultraviolet capabilities of the product. Compared with ordinary high-speed train putty, the putty of the present invention has better anti-ultraviolet ability, better stability and weather resistance, and better meets the driving conditions of rail transit vehicles in high-altitude and high-intensity areas. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The cross-cut test results of the putty obtained in each embodiment and comparative example are shown;

[0036] Figure 2 The UV-visible absorption spectra of the putties obtained in Example 1, Example 4, Example 5 and Comparative Example 2 are shown;

[0037] Figure 3 The UV-visible reflection spectra of the putties obtained in Example 1, Example 4, Example 5 and Comparative Example 2 are shown. DETAILED DESCRIPTION

[0038] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiment.

[0039] Example 1

[0040] This embodiment provides a rail transit putty based on a bio-based unsaturated polyester resin, and the preparation method thereof is as follows:

[0041] Step 1: Preparation of bio-based unsaturated polyester resin

[0042] Add 16 g of diethylene glycol, 15 g of tetrahydrophthalic anhydride, 0.2 g of hydroquinone, 12 g of maleic anhydride, 32 g of styrene for monomer, 12 g of bio-based ethylene glycol, 8 g of bio-based fumaric acid, 12 g of bio-based oleic acid and 5 g of bio-based hydrogenated castor oil into a reactor;

[0043] Introduce nitrogen, start stirring and set the stirring speed to 180 rpm, heat to 170°C and stir for 1 hour. Heat to 200°C and continue stirring at 180 rpm for 1.5 hours; then continue to heat to 210°C and stir at 200 rpm for 3 hours.

[0044] After stirring, the acidity was adjusted to 65KOH / g with a solution prepared with 0.09 g of tert-butyl hydroperoxide and 1.3 g of ethylene glycol monobutyl ether, then the temperature was lowered to 50°C, vacuum-dehydrated for 1 hour, and 2 g of styrene was added for dilution to obtain a bio-based unsaturated polyester resin.

[0045] Step 2: Preparation of putty

[0046] Take 40g of the unsaturated polyester resin prepared in step 1 and 0.7g of the polymerization inhibitor 2,6-di-tert-butyl-4-methylphenol and add them to a high-speed disperser, then add 0.6g of 12% cobalt isooctanoate, stir at a speed of 800r / min for 20 minutes to fully mix the promoter and the resin. Add 0.3g of dispersant sodium fatty acid methyl ester sulfonate, 0.2g of organosilicon defoamer HY-310, 2g of anti-settling thixotropic agent (including 0.4g of KYC-918, 0.4g of fumed silica, 0.4g of montmorillonite, and 0.8g of sodium hydroxymethyl cellulose), set the speed of the high-speed disperser to 1200r / min, continue to disperse for 15 minutes, and then add 2g of styrene for dilution. Then add 48g of silane-coupling modified talc (the mass ratio of 600 mesh to 1000 mesh is 1:1.9) and 2g of acetylated modified alkaline lignin, and stir at a speed of 1400r / min for 2h; finally, add 1.5g of ground titanium dioxide and 2g of styrene, increase the speed of the disperser to 1600r / min, and continue to disperse for 1h. After the high-speed dispersion is completed, let it stand for 0.5h to obtain the atomic putty for rail transit.

[0047] Example 2

[0048] In this example, atomic putty was prepared in the same manner as in Example 1, except that the amount of the accelerator 12% cobalt isooctanoate was reduced from 0.6 g to 0.5 g.

[0049] Example 3

[0050] In this example, atomic putty was prepared in the same manner as in Example 1, except that the amount of the accelerator 12% cobalt isooctanoate was increased from 0.6 g to 0.7 g.

[0051] Example 4

[0052] In this example, atomic ash is prepared in the same manner as in Example 1, with the only difference being that the content of acetylated modified alkaline lignin is increased from 2 g to 3 g.

[0053] Example 5

[0054] In this example, atomic ash is prepared in the same manner as in Example 1, with the only difference being that the content of acetylated modified alkaline lignin is increased from 2 g to 4 g.

[0055] Example 6

[0056] In this embodiment, putty is prepared in the same manner as in embodiment 1, except that the content of the bio-based component in the bio-based unsaturated polyester resin is increased. The specific formula is:

[0057] 16g of diethylene glycol, 15g of tetrahydrophthalic anhydride, 0.2g of hydroquinone, 12g of maleic anhydride, 32g of styrene for monomer, 15g of bio-based ethylene glycol, 10g of bio-based fumaric acid, 15g of bio-based oleic acid, 8g of bio-based hydrogenated castor oil, and 2g of styrene for dilution.

[0058] Example 7

[0059] In this example, putty was prepared in the same manner as in Example 1, except that bio-based acrylic epoxy soybean oil was used instead of styrene as the active diluent.

[0060] Comparative Example 1

[0061] In this comparative example, atomic putty was prepared in the same manner as in Example 1, except that the type of accelerator was replaced by cobalt cyclohexaneate instead of cobalt isooctanoate, and the cobalt content concentration and dosage remained unchanged.

[0062] Comparative Example 2

[0063] In this comparative example, putty was prepared in the same manner as in Example 1, except that no bio-based filler was used, namely, the amount of acetylated modified alkaline lignin added was 0; the anti-settling thixotropic agent consisted of 0.4 g of KYC-918, 0.8 g of fumed silica and 0.8 g of montmorillonite, and sodium hydroxycellulose was not used.

[0064] The putty in the above embodiment and comparative example was mixed and stirred evenly with the cyclohexanone peroxide curing agent at a weight ratio of 100:2, and used for the following performance test:

[0065] (1) Conduct surface drying time test according to GB / T 1728-79 standard.

[0066] (2) Conduct putty film flexibility test according to GB / T 1748-79 standard.

[0067] (3) Perform putty adhesion pull-off test according to ISO 4624 standard.

[0068] (4) Carry out the cross-cut test according to GB / T 9286. Prepare a 0.5 mm thick putty film on the sample coated with primer and dry it for the specified time before testing. The cutting interval is 3 mm. There are 6 levels in total, according to the shedding standard: Level 0 is the best, no shedding; the more serious the shedding, the higher the level.

[0069] (5) Carry out impact resistance test according to GB / T 1732.

[0070] (6) According to GB / T14522, the artificial weathering accelerated test is carried out, using the fluorescent ultraviolet / condensation cycle test method, and the light source is a UV-B (313nm) lamp. The test conditions for each cycle are: UV light, 60℃, 4 hours; condensation, 50℃, 4 hours. After the test is completed for the specified time, the evaluation is carried out according to the evaluation regulations for the comprehensive aging performance level of decorative paint films in GB / T 1766.

[0071] The test results are shown in Table 1.

[0072] Table 1 Performance test results of the putties obtained in various embodiments and comparative examples

[0073]

[0074] It can be seen from Table 1 that a comparative analysis of Example 1, Example 2, and Example 3 shows that when the amount of the accelerator cobalt isooctanoate is gradually increased, the surface drying time is shortened, the curing time is accelerated, and the flexibility is reduced.

[0075] Comparative analysis of Example 1 and Comparative Example 1 shows that the properties of the putty using cobalt isooctanoate as the accelerator are significantly better than those of other cobalt accelerators.

[0076] Example 1, Example 4, Example 5 and Comparative Example 2 were tested for UV-visible absorption spectrum and UV-visible reflection spectrum. The test results are shown in Figure 2 , Figure 3 The test results show that as the amount of modified lignin increases, the product's UV absorption increases, UV reflection decreases, and its anti-UV and anti-aging capabilities are significantly improved, which enhances the product's ability to be used under extreme climatic conditions and meets the resistance and stability of rail transit vehicles under high-altitude and strong sunlight conditions.

[0077] A comparative analysis of Example 1 and Example 6 shows that by increasing the amount of bio-based materials in the unsaturated polyester resin, the obtained putty exhibits better flexibility and impact resistance.

[0078] In addition, the present invention adopts silane coupling modified talc, whose adhesion is far superior to other similar products. The adhesion pulling test shows that the adhesion strength of the product obtained by the present invention is 5.3Mpa on average.

[0079] Finally, it should be noted that the above is only a preferred embodiment of the present invention and not a limitation on the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A rail transit putty based on bio-based unsaturated polyester resin, characterized in that: The preparation method of the atomic ash comprises the following steps: Step 1: Preparation of bio-based unsaturated polyester resin Add 16 g of diethylene glycol, 15 g of tetrahydrophthalic anhydride, 0.2 g of hydroquinone, 12 g of maleic anhydride, 32 g of styrene for monomer, 12 g of bio-based ethylene glycol, 8 g of bio-based fumaric acid, 12 g of bio-based oleic acid and 5 g of bio-based hydrogenated castor oil into a reactor; Nitrogen was introduced, stirring was started and the stirring speed was set to 180 rpm, the temperature was raised to 170°C and stirred for 1 hour; the temperature was raised to 200°C and stirred for 1.5 hours at a stirring speed of 180 rpm; the temperature was further raised to 210°C and stirred for 3 hours at a stirring speed of 200 rpm; After stirring, the acidity was adjusted to 65KOH / g with a solution prepared by 0.09 g of tert-butyl hydroperoxide and 1.3 g of ethylene glycol monobutyl ether, and then the temperature was lowered to 50° C., vacuum-dehydrated for 1 h, and 2 g of styrene was added for dilution to obtain a bio-based unsaturated polyester resin; Step 2: Preparation of putty Take 40g of the unsaturated polyester resin prepared in step 1 and 0.7g of the inhibitor 2,6-di-tert-butyl-4-methylphenol and add them to a high-speed disperser, then add 0.6g of 12% cobalt isooctanoate, stir at a speed of 800r / min for 20 minutes to fully mix the promoter and the resin; add 0.3g of dispersant sodium fatty acid methyl ester sulfonate, 0.2g of organosilicon defoamer HY-310, and 2g of anti-settling thixotropic agent, set the speed of the high-speed disperser to 1200r / min, continue to disperse for 15 minutes, and then add 2g of styrene for dilution; then add 48g of silane-coupled modified talcum powder and acetylated modified alkaline wood 3g or 4g of element, stir continuously at a speed of 1400r / min for 2h; finally, add 1.5g of ground titanium dioxide and 2g of styrene, increase the speed of the disperser to 1600r / min, and continue dispersing for 1; after high-speed dispersion is completed, let it stand for 0.5h to obtain atomic putty for rail transit; wherein, the anti-settling thixotropic agent is composed of 0.4g of KYC-918, 0.4g of fumed silica, 0.4g of montmorillonite and 0.8g of sodium hydroxymethyl cellulose, and the silane-coupled modified talc is compounded by 600-mesh silane-coupled modified talc and 1000-mesh silane-coupled modified talc in a mass ratio of 1:1.

9.

2. An application of the putty according to claim 1 on a vehicle body for rail transit.

Citation Information

Patent Citations

  • Special putty for high speed trains and preparation method thereof

    CN104177901A

  • A high-iron atomic ash and its preparation method

    CN110616005B

  • Special unsaturated polyester resin for automobil putty and preparation method thereof

    CN106866951A

  • Poly putty specially used for multiple unit train as well as preparation method and application thereof

    CN107641365A

  • Polishing putty and preparation method thereof

    CN108707360A